Possible Beneficial Effect of Dapagliflozin in Improvement of Dyspnea Scale (VAS and SA-NYHA Class) in Patients with Acute Decompensated Heart Failure (ADHF) - Hanna Jassim Dohei; Maitham Ali Al-Rikabi (مجلة علوم ذي قار)
Heart failure (HF) is a condition in which the heart is unable to pump enough blood to meet the body's needs. Diuretics are the mainstay of acute heart failure therapy, especially intravenous loop diuretics. In this study, IV.furosemide (120mg/day) plus 10mg dapagliflozin tablet were used daily. The aim of the present study is to observe the Possible beneficial effect of dapagliflozin in the improvement of dyspnea scale (VAS and SA-NYHA Class) in patients with ADHF. Between October 2023 and April 2024, a study was conducted at AL- Nasiriyah Heart Center, in the coronary care unit (CCU), in , southern of Iraq. One hundred subjects, both male and female were enrolled in the study after describing the study's goals, gauging patient satisfaction, and getting informed consent from the subjects. 100 enrolled patients were divided into two groups: The control group (Group A) involved (50 patients), given IV.furosemide (120mg/day) and the studied group (Group B) involved (50 patients), given IV. furosemide (120 mg/day) plus 10mg dapagliflozin tablet daily. Then, it was the assessment of symptoms of dyspnea by Visual Analog Scale and SA-NYHA class. It was found that dyspnea scales (VAS and SA-NYHA Class ) for patients in both groups (A and B) at hospital admission were significantly improved after subsequent days of admission.